Studying for a University Degree in Penitentiary Centers in Spain: Challenges and Difficulties From the Internee's Perspective. (November 2019) - Vazquez-Cano, Esteban; Holgueras-González, Ana Isabel; Fombona-Cadavieco, Javier
This article describes research undertaken in three penitentiary centers in Spain to analyze the expectations, motivations, and obstacles of internees in a university degree program of the Universidad Nacional de Educacion a Distancia ([National University of Distance Education]; UNED). Utilizing a qualitative method through interviews, the results show that the main expectation for getting a higher education qualification is to improve and give meaning to daily life in prison. Obstacles include difficulty of access to, and lack of relevant information on, the UNED online study platform.